The Right of Americans to be Protected from Gun Violence - Thomas Gabor, Ph.D. (Washington University Journal of Law & Policy, 2021)
The unrelenting gun violence faced by Americans has reached virtually every setting including Walmarts, festivals, entertainment districts, schools, places of worship, and work places. Altercations involving firearms are far more likely to end in death than those involving other weapons or no weapon at all. Historically, the Second Amendment to the United States Constitution was interpreted as the right to bear arms within the context of military service. In Heller, the Supreme Court ruled that individuals had the right to own an operable gun in their homes for protection. However, the Court made clear the right was not unlimited and that gun ownership could be denied to felons and the mentally ill. Gabor addresses whether the public has the right to be protected from gun violence in their community. Gabor argues that social theory, the Declaration of Independence, and a myriad of other sources require national and state governments to be held accountable for the public safety in the face of gun violence.
Keywords: gun; guns; gun violence; protection; right to protection; public safety; Second Amendment; Heller; District of Columbia v. Heller